EFFECTS OF ENTREPRENEURIAL BEHAVIORS AND PRODUCT INNOVATION PERFORMANCE TOWARDS START-UP BUSINESS SURVIVAL IN THAILAND - Pimsuwan, Hassadee; PHOSAARD, Satidchoke; SUNGSANIT, Mullika (Asian Administration and Management Review, 2023)
This research aims to: 1) study the magnitude of the effects of entrepreneurial behaviors towards start-up business survival in Thailand and 2) study the magnitude of product innovation performance towards start-up survival in Thailand. The target groups are among founders of start-up businesses in Thailand. The questionnaire was used as a tool for collecting data. Data were analyzed by quantitative analytical methods including mean, standard deviation, and using binary logistic regression modeling. The results indicated that finding and refining the opportunity was the highest, followed by identifying and selling to customers, operating the business, strategic performance, customer performance and outside of the business. Moreover, it was found that acquiring resources and help, market performance and financial performance contributed a positive impact on start-up survival in Thailand.